GIS-material for the archaeological project: Survey preceding contruction and rebuilding of houses, and cycle and foot path - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to construction and rebuilding of houses, and along a planned foot and cycle path, the Swedish National Heritage Board's Contract Archaeology Division, UV Öst, has performed an archaeological assessment in the city and municipality of Linköping. Except for stray finds of modern character such as bricks, glass, pieces of metal, faience and porcelain in an older agricultural layer, as well as a few modern pits, nothing of archaeological interest was found in the survey area.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of an archaeological assessment, stage 2, is to determine whether any archaeological remains will be affected by the development works.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför ny- och ombyggnad av fastigheter och i planerad GC-vägs sträckning i Linköpings stad och kommun utförde Riksantikvarieämbetet UV Öst en arkeologisk utredning. Utöver spridda yngre fynd som tegel, glas, metallbitar, fajans och porslin i en äldre åkerhorisont, samt ett par yngre nedgrävningar, fanns inom utredningsområdet inget av antikvariskt intresse.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
En arkeologisk utredning, etapp 2, syftar till att avgöra om lagskyddad fornlämning berörs av exploateringsföretaget.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Inför ny- och ombyggnad av fastigheter och gång- cykelväg
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi